Testing biobeds as a possible solution for the biodepuration of pesticide-contaminated wastewaters produced by various agro-industries - Karas, P. A. (2017)
Several agro-industries produce pesticide-contaminated wastewaters which constitute a serious point source for the contamination of natural water resources. Hence they should be treated prior to their disposal. Βiobeds could be a viable solution for the depuration of such effluents. In the frame of evaluation of biobeds to treat effluents produced by different agro-industrial processes (ornamental bulb dipping, seed-coating, and fruit packaging) we aimed to investigate the dissipation of pesticides contained in those effluents. The biomixture utilized was known to be effective in the treatment of wastewaters from the fruit packaging industry, and it is composed of soil, straw and spent mushroom substrate (SMS) in a 1:1:2 volumetric ratio. Sub-samples of the biomixture were treated with aqueous solutions of fludioxonil (FDL-obc, 20 mg/kg), chlorothalonil (CHT, 50 mg/kg) orthiabendazole (TBZ 20 mg/kg) at dose rates relevant for bulp dipping; fludioxonil (FDL-sc, 10 mg/kg), carboxin (CBX, 52 mg/kg), metalaxyl-M (MET, 28 mg/kg) and fluxapyroxad (FLX, 34 mg/kg) at dose rates relevant in seed coating; fludioxonil (FDL-fpi, 150 mg/kg) at a dose rate relevant in fruit-packaging. Pesticides were applied individually while certain combinations, relevant for practical reasons were also assessed. Preliminary results (up to 14 days) suggested a rapid loss of CBX and CHT with 96.4 and 91.3% of their initial applied amount being dissipated, respectively. In contrast, FDL exhibited a low dissipation in the same period, with only 30.3% in the FDL-sc treatment, while no appreciable dissipation was observed in the FDL-obc and FDL-fpi treatments at the same period. Our findings provide preliminary evidence that a biomix composed of SMS, soil and straw could be effective in the dissipation of pesticides contained in effluents produced by seed coating or bulb dipping activities. The complete dataset will be presented and discussed in the conference.